2011
DOI: 10.1002/hbm.21083
|View full text |Cite
|
Sign up to set email alerts
|

Application of whole‐brain CBV‐weighted fMRI to a cognitive stimulation paradigm: Robust activation detection in a stroop task experiment using 3D GRASE VASO

Abstract: Brain activation studies generally utilize blood oxygenation level dependent (BOLD) contrast, most commonly measured using the gradient-echo echo-planar imaging (EPI) technique. BOLD contrast arises from regional changes in cerebral blood flow (CBF), cerebral blood volume (CBV), and the local metabolic rate of oxygen consumption. An alternative to BOLD is the detection of activation through direct measurement of these parameters. A noninvasive approach to measure activation-related CBV changes is the vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…The total acquisition time for both resting and task scan was 8 min and 30 s. TI was determined based on the blood T 1 of 1627 ms (Lu et al, 2004;Poser and Norris, 2011). A gradient-echo EPI sequence was used for BOLD imaging acquisition.…”
Section: Vaso and Bold Data Acquisitionmentioning
confidence: 99%
“…The total acquisition time for both resting and task scan was 8 min and 30 s. TI was determined based on the blood T 1 of 1627 ms (Lu et al, 2004;Poser and Norris, 2011). A gradient-echo EPI sequence was used for BOLD imaging acquisition.…”
Section: Vaso and Bold Data Acquisitionmentioning
confidence: 99%
“…In the following years, several other groups became interested in this technology and made important contributions to its optimization and understanding. These include the combination of VASO with ASL/BOLD acquisitions (Yang et al, 2004), the use of tissue-nulling TIs (Shen et al, 2009; Wu et al, 2008), the use of multiple TIs to simultaneously estimate resting and activated CBV (Glielmi et al, 2009; Gu et al, 2006), the imporved suppression of blood signal (Wu et al, 2007), the use of VASO in calibrated fMRI (Lin et al, 2008a), the effect of CSF contributions on VASO signal (Scouten and Constable, 2007, 2008), the spatial specificity of the signal (Jin and Kim, 2008), and the design of methods for faster acquisition and greater spatial coverage of VASO (Poser and Norris, 2007, 2009, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…With recent advances in image acquisition and reconstruction approaches as well as hardware improvement, it is now possible to acquire 3D volumes after a slab-selective RF excitation. Poser and Norris showed that single-shot 3D GRASE can be used for VASO acquisition, which covered 20 slices with 3.5×3.5×5 mm 3 spatial resolution (Poser and Norris, 2011). Reliable activations were observed during a cognitive paradigm, Stroop color-word matching task.…”
Section: Introductionmentioning
confidence: 99%
“…Проводили валидационные исследования по сравне-нию VASO с более традиционными методиками, в т. ч. с использованием наночастиц монокристаллического оксида железа (MION)-CBV [106], усиливающими чувс-твительность VASO к CBV: ПЭТ CBV [21], и Gd-DSC [22]. Методику VASO применяли в ряде исследований нейрососудистой связи [108] и исследованиях методоло-гии функциональной МРТ [109][110][111][112], а также в клинике при окклюзионно-стенотических заболеваниях [22,70] болезни Альцгеймера [113] и раке [114,115].…”
Section: объем церебральной кровиunclassified